Coherent energy and charge carrier dynamics In quasi-2D lead halide perovskites - Ramesh, Sankaran (Nanyang Technological University, 2023)
Halide Perovskites are versatile materials for photovoltaic and light emission applications thanks to their outstanding optical properties. While the three-dimensional halide perovskites evolved to become the archetypal system over the past decade, their two-dimensional (2D) and quasi-2D analogues have prompted interest recently, thanks to novel physics originating from their multiple quantum well structure. The ultrafast energy transfer or funnelling from high- to low-bandgap layers is a widely studied phenomenon in quasi-2D perovskites. Controlling funnelling by modulating the perovskite composition has been shown to enhance film properties and produce efficient light emitters and stable solar cells. However, the origin and mechanism behind the funnelling remains nebulous, with multiple reports assigning the process to F¨orster resonance energy transfer and electron/hole transfer with varying timescales.